Mengembangkan Permainan Bowling Angka untuk Meningkatkan Kemampuan Berhitung Permulaan Anak Kelompok A di Paud Adrikna Selen Aik Kecamatan Narmada Tahun 2021 - Mia Ilhami Azizah; Ika Rachmayani; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2022)
Early childhood numeracy skills are the abilities possessed by each children related to simple mathematical concepts, related to the introduction of the concept of a number and number symbols as well as simple addition and subtraction. The purpose of this study was to determine the efforts to develop a number bowling game that can improve the initial arithmetic ability of group A children at PAUD Adrikna Selen Aik, Narmada District in 2021. This type of research is a development research with three stages of development, each of which consists of planning, implementation, observation, and analysis of development. Subject This research is group A children, totaling 10 children. Method collection data using the method of observation and documentation. The data analysis technique used descriptive qualitative analysis. The results of the research on the application of the number bowling game show that the average early arithmetic ability of children increases, namely in the first development 50,8% then development II. 79,1% and development III 93,9%.  The conclusion is that the application of the number bowling game can improve the initial numeracy skills of group A children at PAUD Adrikna Selen Aik Narmada District in 2021.